Impact of drill cutting releases on benthic foraminifera at three exploration wells drilled between 1992 and 2012 in the SW Barents Sea, Norway. (January 2020) - Dijkstra, Noortje; Junttila, Juho; Aagaard-Sørensen, Steffen
Abstract: The aim of this study is to identify the environmental impact of drill cuttings (DC) released around three wells drilled in 1992, 2000 and 2012 in the SW Barents Sea. Foraminiferal assemblages are studied in cores taken along transects <250 m from wells. Well E-1992 shows no impact of DC on foraminifera indicating that low amounts of released DC limit environmental impact. Impact at wells G-2000 and S-2012, is confined to <30 m, and attributable to smothering of fauna, resulting in low foraminiferal density. We therefore argue that previous monitoring studies, mainly focusing on samples collected >250 m from wellheads, might not capture the full impact of DC. In well G-2000, a recovery layer indicates partial recovery 15 years after DC releases. In well S-2012, no recovery is observed, 3 years after release. Released DC did not result in faunal composition changes. Highlights: Environmental impact of drill cuttings around wells in Barents Sea is investigated. The environmental impact is confined to <30 m from the wellhead. Main impact on foraminifera is attributed to smothering of fauna. No changes in foraminiferal faunal composition due to drill cuttings are observed. Partial environmental recovery is observed 15 years after release.